The assessment of isometric, dynamic, and sports-specific upper-body strength in male and female competitive surfers - Parsonage, J.; Secomb, J.; Dowse, R.; Ferrier, B.; Sheppard, J.; Nimphius, S. (Sports, 2018)
The primary purpose of this study was to investigate gender differences in the dynamic strength index (DSI): an assessment of upper-body dynamic strength relative to maximal isometric strength. The secondary purpose was to investigate gender differences in the dynamic skill deficit (DSD): an assessment of sports-specific dynamic strength relative to maximal isometric strength, and its association with a sports-specific performance measure in surfers. Nine male (age = 30.3 ± 7.3 yrs) and eight female (age = 25.5 ± 5.2 yrs) surfers undertook three upper-body assessments: isometric push-up, dynamic push-up, and a force plate pop-up to determine the DSI and DSD. The performance measure of time taken to pop-up (TTP) was recorded. No gender differences for the DSI (d = 0.48, p = 0.33) or DSD (d = 0.69, p = 0.32) were observed. Normalized peak force (PF) of the isometric push-up, dynamic push-up, and force plate pop-up were significantly greater in males (p = 0.05), with males recording significantly quicker TTP (d = 1.35, p < 0.05). The results suggest that male and female surfers apply a similar proportion of their maximal strength in sports-specific movements. However, greater normalized isometric and dynamic strength in males resulted in greater sports-specific PF application and a faster TTP. It would appear favorable that female surfers improve their maximal strength to facilitate sports-specific pop-up performance